Development of Interactive Multimedia for Informatics Learning in Manado State 6 Junior High School - Bahrun, Lusi Maryana; Rompas, Parabelem Tinno Dolf; Oroh, Rolly Robert (International Journal of Information Technology and Education, 2023)
The development of the Industrial Revolution 4.0 has brought changes, where students can take advantage of technological advances in this revolution by accessing the internet to look for learning resources either through websites or YouTube. This research aims to (1) develop interactive multimedia learning in informatics learning for class VII students, (2) determine the feasibility of interactive multimedia for class VII informatics learning (3) find out students' responses regarding interactive multimedia in learning. This interactive multimedia development uses the Research and Development (R&D) method, and the APPED development model with steps (1) analysis and initial research, (2) design, (3) production, (4) evaluation, and (5) dissemination. Respondents to research on the development of interactive multimedia for informatics learning were class VII of SMP Negeri 6 Manado. The results of the research that has been carried out show that: (1) interactive multimedia on computational thinking material was created and developed using Google Sites. (2) The results of the assessment of the feasibility of learning multimedia obtained a percentage of feasibility in alpha testing, namely the assessment from material experts was 82.50% categorized as very feasible, the assessment from media experts was 91.25% categorized as very feasible, beta testing with assessments from average users feasibility, namely 85.77%, falls into the very feasible category. (3) Respondents' comments regarding this multimedia product were very diverse, namely suggestions for improving this interactive multimedia and responses that this interactive multimedia was needed for learning activities. Based on the respondents' responses and the assessment results from the questionnaire, interactive multimedia is used and needed by students in learning at SMP Negeri 6 Manado.